The canons of fantasy lands of high adventure - Moran, Patrick 1981- (Cambridge University Press, 2019)
Despite publishing endeavours such as the Ballantine Adult Fantasy Series in the 1970s and Fantasy Masterworks in the early 2000s, the canon of modern fantasy is still very much in flux. This Element examines four key questions raised by the prospect of a fantasy canon: the way in which canon and genre influence each other; the overwhelming presence of Tolkien in any discussion of the classics of fantasy; the multi-media and transmedia nature of the field; and the push for a more inclusive and diverse canon
Keywords: Fantasy fiction / History and criticism; Fantasy fiction / Publishing / History / 20th century; Fantastische Literatur; Canon (Literature); Fantasy fiction; Criticism, interpretation, etc